Limitations of the Reconfiguration and Applicability of Citizenship Rights in the Mixed Model of Hegemony and Democracy Underway in Contemporary Africa - Jesus A. Tomé, (Global Journal of Human-Social Science, 2024)
This study which has as its problematic the analysis of the dynamic developments of citizenship rights on the African continent from the fall of authoritarian state institutions to the context of democratic openings aims to show the limitations that exist within the scope of the reconfiguration and applicability of citizenship rights in contemporary Africa due to the adoption of ambiguous political models that are simultaneously hegemonic and democratic This study is a qualitative theoretical approach developed through exploratory bibliographic research The results indicate that the democracy achieved in Africa reveals a democratic and an authoritarian nature as a result of the presence of non-democratic elements that have accompanied the different political systems tested on the continent in which the degree of applicability of rights of Citizenship depends on the ruling elite and the perceived level of threat to their maintenance in power From these results we conclude that even so in this context it is relatively early to declare the failure or success of both democracy and citizenship rights For all intents and purposes this is a process under definition whose contours are not yet entirely fixed and it is naturally not possible to exclude the possibility that as in the past other options will be tested perhaps less democratic and as a consequence of this less favorable to promoting the values and practices of citizenship